Defamilization/familization measures and women's pension income—The case of Taiwan. Issue 2 (20th March 2017) - Chau, Ruby C. M.; Foster, Liam; Yu, Sam W. K.; Yu, Yuk Pun
Abstract : This paper examines how defamilization and familization measures can affect women's capacity to accumulate pension income and their subsequent standard of living after retirement. Firstly, it highlights the concepts of defamilization and familization and discusses the potential of these measures in assisting women to save pension income through the "commodification" and "decommodification" of labor. Secondly, it examines the major pension policies and examples of defamilization and familization measures in Taiwan. It shows how the current limited provision of such measures could create "double jeopardy" for women, affecting access to paid employment or resources to enable women who wish to undertake caring responsibilities to do so, ultimately impacting their capacity to accumulate pension income. Thirdly, it suggests ways to strengthen defamilization and familization measures in order to enable women to accumulate sufficient retirement income on the basis of three preconditions: policy attention to the reciprocal relationship between familization/defamilization measures and pension schemes for women; a recognition of differences between women in their preferred strategies to accumulate pension income; and an emphasis on a life course perspective to understand the double jeopardies faced by women in saving for retirement.